2021
DOI: 10.3390/geosciences11070280
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Characterization of Fracture Patterns: A Case Study of the Noble Hills Range (Death Valley, CA, USA), Application to Geothermal Reservoirs

Abstract: In the basement fractured reservoirs, geometric parameters of fractures constitute the main properties for modeling and prediction of reservoir behavior and then fluid flow. This study aims to propose geometric description and quantify the multiscale network organization and its effect on connectivity using a wide-ranging scale analysis and orders scale classification. This work takes place in the Noble Hills (NH) range, located in the Death Valley (DV, USA). The statistical analyses were performed from region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 59 publications
1
34
0
Order By: Relevance
“…Thus, Section 4.1 of this study will give new elements, improving the observations made by [38,41] concerning the NH structure. A precise fracture pattern characterization of the NH was performed by [42], through a wide-ranging analysis scale from the microscopic scale to the regional scale. These authors showed that the NH fracture network geometry has been controlled by the SDVFZ and the GFZ.…”
Section: Geological Settingmentioning
confidence: 99%
“…Thus, Section 4.1 of this study will give new elements, improving the observations made by [38,41] concerning the NH structure. A precise fracture pattern characterization of the NH was performed by [42], through a wide-ranging analysis scale from the microscopic scale to the regional scale. These authors showed that the NH fracture network geometry has been controlled by the SDVFZ and the GFZ.…”
Section: Geological Settingmentioning
confidence: 99%
“…It increases in intensity where the NH range converges with the Avawatz mountains ( [38] and references therein), at the intersection between the SDVFZ and the GFZ [30]. Chabani et al (2021) [12] have identified E-W structures in this area and they suppose that these structures are linked to the activity of the GFZ and the convergence of the Avawatz and the NH range. It is tempting to propose that this convergence implied the elevation of the topography at the southern part of the NH range.…”
Section: Thermal Evolution Of the Nh Granitementioning
confidence: 99%
“…In that case, the magmatic texture is preserved. These faults are striking mainly NW/SE (SDVFZ direction) ( [12], this issue). In order to be more precise in the sample selection, this latter was also based on the degrees of microfracturing defined by [44], from microscopical observations.…”
Section: Materials and Sampling Strategymentioning
confidence: 99%
See 2 more Smart Citations